Dehydration and hyponatremia in professional rugby union players: A cohort study observing English Premiership rugby union players during match play, field, and gym training in cool environmental conditions - Jones, B. L.; O'Hara, J. P.; Till, K.; King, R. F. G. J. (The Journal of Strength and Conditioning Research, 2015)
Fluid and sodium balance is important for performance and health; however, limited data in rugby union players exist. The purpose of the study was to evaluate body mass (BM) change (dehydration) and blood[Na+] change during exercise. Data were collected from 10 premiership rugby union players, over a 4-week period. Observations included match play (23 subject observations), field (45 subject observations), and gym (33 subject observations) training sessions. Arrival urine samples were analyzed for osmolality, and samples during exercise were analyzed for [Na+]. Body mass and blood[Na+] were determined pre- and postexercise. Sweat[Na+] was analyzed from sweat patches worn during exercise, and fluid intake was measured during exercise. Calculations of fluid and Na+ loss were made. Mean arrival urine osmolality was 423 ± 157 mOsm/kg, suggesting players were adequately hydrated. After match play, field, and gym training, BM loss was 1.0 ± 0.7, 0.3 ± 0.6, and 0.1 ± 0.6%, respectively. Fluid loss was significantly greater during match play (1.404 ± 0.977 kg) than field (1.008 ± 0.447 kg, p = 0.021) and gym training (0.639 ± 0.536 kg, p < 0.001). Fluid intake was 0.955 ± 0.562, 1.224 ± 0.601, and 0.987 ± 0.503 kg during match play, field, and gym training, respectively. On 43% of observations, players were hyponatremic when BM increased, 57% when BM was maintained, and 35% when there was a BM loss of 0.1-0.9%. Blood[Na+] was the representative of normonatremia when BM loss was >1.0%. The findings demonstrate that rugby union players are adequately hydrated on arrival, fluid intake is excessive compared with fluid loss, and some players are at risk of developing hyponatremia.